2017
DOI: 10.3171/2017.5.peds17116
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of a large ruptured middle cerebral artery bifurcation aneurysm in a 5-week-old infant: case report

Abstract: Ruptured intracranial aneurysms are extremely rare in infants. The optimal treatment strategy is not well established. Both microsurgical and endovascular techniques and strategies have been tried, and in the literature there is a significant variability in outcome. The authors report the presentation and successful endovascular treatment of a large, ruptured, middle cerebral artery bifurcation aneurysm in a 5-week-old girl, one of only a few reported in the literature. Clinical and radiological findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…1,4,5,[7][8][9]15 On the other hand, saccular aneurysms are rare and only eight cases have been treated by embolization in patients under 30-month-old with good results. 16 EVT cases have been performed during the first 2 months of life in only two cases. 17 Regarding their location, the internal carotid artery bifurcation followed by middle cerebral artery is the more common site in the anterior circulation.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5,[7][8][9]15 On the other hand, saccular aneurysms are rare and only eight cases have been treated by embolization in patients under 30-month-old with good results. 16 EVT cases have been performed during the first 2 months of life in only two cases. 17 Regarding their location, the internal carotid artery bifurcation followed by middle cerebral artery is the more common site in the anterior circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior circulation aneurysms account for 17-21 of pediatric aneurysms [1,3], and within this group 24 are less than 12 months of age [5]. A recent a review of ruptured aneurysms in infants found only two reports of posterior circulation aneurysms [6].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of third ventricle bowing, especially third ventricle floor bowing, suggests compliant third ventricle walls and a pressure difference between the third ventricle and the subarachnoid space, which indicate an intraventricular obstructive hydrocephalus and can result higher ETV success. 1 We believe that in patients with chronic hydrocephalus, even if without signs of acutely elevated ICP and transependymal flow, preoperative third ventricle floor bowing can still reflect good compliance of the third ventricle wall and a pressure difference between the ventricle and the subarachnoid space, and these patients therefore can still be treated successfully with ETV.…”
Section: Preoperative Third Ventricle Shape and Etvmentioning
confidence: 93%
“…Foroughi et al 2 reported an ETV success rate of 96% in patients with preoperative lamina terminalis and third ventricle floor bowing. Dlouhy et al 1 also found that preoperative third ventricle bowing was a good predictor of ETV success, and they reported that patients with third ventricle bowing had a 3-fold likelihood of success compared with those without such bowing. The existence of third ventricle bowing, especially third ventricle floor bowing, suggests compliant third ventricle walls and a pressure difference between the third ventricle and the subarachnoid space, which indicate an intraventricular obstructive hydrocephalus and can result higher ETV success.…”
Section: Preoperative Third Ventricle Shape and Etvmentioning
confidence: 96%